Cálculo de la capacidad del enlace de subida en LTE-Advanced con agregación de portadoras inter banda - Calderón Choy, José Luis (2014)
This thesis aims to calculate the total capacity of the terminal equipment in the uplink for LTE-Advanced carrier aggregation intraband and interband according to 3GPP Release 11 and for this it is necessary to select an appropriate propagation model that allows obtaining the SNR and then determines the modulation of each carrier to be added , and finally calculate the capacity. For the calculation of the capacity, we have designed a web application that follows the parameters of Release 11 for carrier aggregation. It specifies the existing carrier aggregation types, and also the confugurations and combination. After making the channeled of each carrier, for carrier aggregation intraband continuous, the channel separation is evaluated. Then, knowing the terminal class and using the propagation model Cost-231 Hata and reference sensitivity in the link budget for the uplink, the cells of the adaptative modulation are calculated and then the capacity of each modulation cell to each component carrier. Finally, the total capacity is calculated in the uplink for carrier aggregation.